The value of ethnography and the comparative case study approach in VET research : exemplified by the project "VET cultures in a European comparison" - Gericke, Erika E. [Verfasser] (My University, 2020)
"This methodological contribution argues for considering an ethnographical approach in comparative vocational education and training (VET) research and illustrates its usefulness with the study "VET cultures in a European comparison". This ethnographic comparative study uses lesson observations, guided interviews and photographs in order to investigate how educational traditions shape the social practices of teaching and learning in vocational classes/courses for car mechatronics and office management in England and Germany. With the analysis of the first of four sets of data, a need for an analytical framework for the ethnographic comparative VET study arose in order to systematise the first emerging findings. Thus, the second part of the contribution scrutinises the usefulness of the comparative case study (CCS) approach by Bartlett and Vavrus (2017) by applying it to the ethnographic comparative study on "VET cultures in a European comparison". This contribution shows that for comparative VET research, which deals with learning and teaching practices, an ethnographic approach is a promising approach and that the CCS approach is a helpful analytical framework for systematising empirical results of comparative studies." (author's abstract ; BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; G 1.2.3 Qualifikationsentwicklungen; S 6.2.3 Metallerzeugung und -bearbeitung, Maschinenbau, Montierberufe (inkl. fahrzeugtechnischer Berufe); S 6.4.1.2 Dienstleistungskaufleute; I 2.2.1 Westeuropa; Vergleichende Berufsbildungsforschung; Kompetenzentwicklung; Berufsschule; Kraftfahrzeugmechatroniker; Bürokaufmann; Ethnologie; Fallstudie; Großbritannien; Bundesrepublik Deutschland